(untitled) (XXI Century. Spanish Literature and Culture, 2008)
The parody has transcended its old connotation of mockery, but without losing its relationship with humor and irony, to acquire a constructive mode, based on imitation, copying and deformation, transforming itself into a modality utilized by the novel to dialogue with literary genres and other artistic expressions and manifestations of popular culture, to express the many facets of the complex contemporary society. In Luis Landero’s El guitarrista parodic exercise forms part of the narrative structure and allows the author to generate humor, irony, critique and to develop a personal vision of reality. Landero’s text is a parody of a novel of initiation: A teenage boy makes the transition to adulthood painfully, by a romantic disappointment. The structure of this kind of story does not deform in the novel, but simply shades it, retaining the essential elements of the model, to transcend and become a reflection on art and literature, as the parodic becomes a metatextual exercise that explains the creative process, the intellectual work of the author and the transcendence of the literary work in contemporary society.